As fontes filosóficas do pensamento de Mauricio Tragtenberg: inventário e subsídios para compreensão de uma filosofia de combate - Phintener, Marcelo de Jesus (2021)
This research, transformed into a dissertation, tried to inventory the theoretical-philosophical bases of Tragtenberg’s thought, investigating traits of thinkers, in particular those of political philosophy who, in some way, were involved in the composition of his work. In turn, and given its great relevance, the investigation of the sources broadened the horizons of study by addressing two hypotheses: one rests on the idea of a political philosophy in Tragtenberg’s work, as the work place is pointed out as a political unit; another, it presupposes the existence of an interpretive framework for the capitalist exploitation of labour, based on concrete analysis, via the column “No Batente”. These three points are interconnected and complement each other in the purpose of the research, as they will highlight the philosophical bases of the author of revolutionary inspiration, not as contemplation, but as a “practical-critical” action. In the whole of his work, in which he proceeds so much with a critical view of capitalism, combined with an analysis of the ambiguities of workers' movements, the result of dialectical and assiduous readings of authors of political science and history, sociology and economics, literature and philosophy, and business administration, Tragtenberg goes from the popular to the classic, combining formal and informal knowledge, theory and practice. A thinker anchored in economic history and, above all, in the analysis of social relations of work and economic exploitation, examining its development in the history movement, always aware of its implications for workers’ standard of living, Tragtenberg, therefore, never lost sight of the real problems of life as a decisive aspect of society. After delineating the dissertation content, it was noticed that the research on screen opens, on the one hand, the first research on the author's ideas in the framework of philosophy; on the other hand, it contributes to the reflection about the relevant diversity in the historiography of political and philosophical thought, since such research, when investigating the trajectory of Tragtenberg philosophical influences, confirms it among the main Brazilian thinkers